Factors affecting hematological profiles in three Ethiopian indigenous goat breeds - Tibbo, Markos; Jibril, Y.; Woldemeskel, M.; Dawo, F.; Aragaw, K.; Rege, J.E.O. (Veterinary Solutions LLC, 2004)
Hematological parameters were studied in 163 apparently healthy goats comprised of 3 indigenous breeds at Adami-Tulu Agricultural Research Centre (ATARC) and Sheno, Agricultural Research Centre (SARC), Ethiopia. Data were analyzed for the effect of breed, sex, age, and season. Hemoglobin (Hb) was significantly higher (P < 0.0001) for Arsi-Bale (AB) than Longeared Somali (LES) and Central Highland (CH) goats. Packed cell volume (PCV) was significantly lower (P < 0.0001) for LES than the other two breeds. White blood cells (WBC) (P < 0.05), neutrophils (P < 0.0001) and basophils (P < 0.0001) were higher in CH than in the other two breeds. Conversely, lymphocytes were lowest (P < 0.0001) in CH goats compared to other breeds. Female goats had significantly (at least P < 0.05) higher red blood cells (RBC), PCV, WBC, lymphocytes and eosinophils than male goats. In contrast, males had higher (P < 0.05) mean corpuscular hemoglobin (MCH) and neutrophils than females. There was no significant age difference for the erythrocytic series but the age difference was highly significant (P < 0.0001) for the leukocytic series. WBC and lymphocytes decreased as age increased while the reverse was true for neutrophils and eosinophils. Seasonal variation was also considerable for both erythrocytic and leukocytic series. RBC, Hb, lymphocytes, and neutrophils of the indigenous goat breeds were remarkably different compared to most other exotic goat breeds.